KAPASITAS PRODUKSI BUBUR KEDELAI BAHAN BAKU TAHU DENGAN VARIASI DEBIT AIR PROSES PENGGILINGAN - Widiyarta, I. M.; Parwata, I. M.; Putra, W.; Wirayoga, A. A. G. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
Soybean grinding machine has been used by many small industrial for tofu production to increase productivity. The addition of the water container with tap water on soybean grinding machine intended to help the soybean grinding process becomes faster and constant. How the changing of the flow water is can affect the speed of production need to research in order to make predictions of tofu production. In this article, the extra water in the process of grinding soy is regulated varies (by opening the tap water of 30°, 45°, 60°, 75° and 90° (full aperture)) to determine the speed of the production of soy porridge with tofu raw materials. The result has shown the greater water discharge the faster the soy pulp production process.
Keywords: small industry, grinder soybeans, soy porridge, tofu